Labor, land, and the global dynamics of economic inequality - Amy Bogaard; Pablo Cruz; Mattia Fochesato; Jennifer Birch; Gabriela Cervantes Quequezana; Shadreck Chirikure; Enrico R. Crema; Gary M. Feinman; Adam S. Green; Helena Hamerow; Guiyun Jin; Tim Kerig; et al. (Proceedings of the National Academy of Sciences, 2025)
Here, we assess the extent to which land use relating to food acquisition (farming, herding, foraging) and associated value regimes shaped past economic inequality. We consider the hypothesis that land-use systems in which production was limited by heritable material wealth (such as land) sustained higher levels of inequality than those limited by (free) human labor. We address this hypothesis using the Global Dynamics of InequalIty (GINI) project database, estimating economic inequalities based on disparities in residential unit area and storage capacity within sites in different world regions and through time. We find that inequality was significantly greater in land-limited than labor-limited regimes, whether based on residence area or storage capacity, though governance could moderate these differences. Increasing inequality with larger residence and/or site size is associated with underlying shifts from labor- to land-limited economies. Transitions from labor- to land-limited regimes also appear to underlie the development of extended political hierarchies. Increases in inequality after cultivation became common in each hemisphere similarly reflect shifts from labor- to land-limited systems. Land-limited systems in the eastern hemisphere, incorporating animal traction, exhibit an upward trend in inequality over time, while a downward trend in the western hemisphere reflects the lower persistence of land-limited regimes based solely on human labor.